Social Anxiety of Youth Prisoners and Guidance and Counseling Services for Prevention - Alizamar Alizamar; Miftahul Fikri; Afdal Afdal (Program Studi bimbingan Konseling PPs UNM Makassar, 2017)
Various juvenile delinquencies today lead them to the realm of law so they go to jail. The government has sought to provide coaching for juvenile inmates so that they are ready to enter new life once free, but the coaching that has been implemented has not been able to optimally reduce the problems of juvenile inmates. One of the problems that juvenile inmates face is the feeling of excessive fear and anxiety unacceptable in the social environment after being released from prison, which is also called social anxiety. For that, it takes a variety of understanding and appropriate programs to overcome social anxieties of juvenile inmates who can be done through counseling and counseling services This paper discusses the basic concepts of social anxiety and the importance of counseling and guidance services